Utilization of health care services for childhood morbidity and associated factors in India: a national cross-sectional household survey. - Chandrashekhar T Sreeramareddy (Public Library of Science (PLoS), 2012)
Background Information about utilization of health services and associated factors are useful for improving service delivery to achieve universal health coverage. Methods Data on a sample of ever-married women from India Demographic and Health survey 2005-06 was used. Mothers of children aged 0-59 months were asked about child's illnesses and type of health facilities where treatment was given during 15 days prior to the survey date. Type of health facilities were grouped as informal provider, public provider and private provider. Factors associated with utilization of health services for diarrhea and fever/cough was assessed according to Andersen's health behavior model. Multinomial logistic regression analyses were done considering sampling weights for complex sampling design. Results A total of 48,679 of ever-married women reported that 9.1% 14.8% and 17.67% of their children had diarrhea, fever and cough respectively. Nearly one-third of the children with diarrhea and fever/cough did not receive any treatment. Two-thirds of children who received treatment were from private health care providers (HCPs). Among predisposing factors, children aged 1-2 years and those born at health facility (public/private) were more likely to be taken to any type of HCP during illness. Among enabling factors, as compared to poorer household, wealthier households were 2.5 times more likely to choose private HCPs for any illness. Children in rural areas were likely to be taken to any type of HCP for diarrhea but rural children were less likely to utilize private HCP for fever/cough. 'Need' factors i.e. children having severe symptoms were 2-3 times more likely to be taken to any type of HCP. Conclusion Private HCPs were preferred for treatment of childhood illnesses. Involvement of private HCPs may be considered while planning child health programs. Health insurance scheme for childhood illnesses may to protect economically weaker sections from out-of-pocket health expenditure during child illness.